Protein networks and analysis of global gene expression - Ideker, Trey (Henry Stewart Talks, 2007)
A paradigm shift: from databases of protein sequences to protein interactions, Technologies for measuring interactions, Chromatin immunoprecipitation (ChIP), Yeast Two Hybrid (Y2H) technology, Mass spectrometry based approaches, Methods for querying protein networks with gene expression profiles, Systematic validation of protein network models using gene deletions, Cytoscape open-source software for network modeling and visualization, Methods for network comparison across species, Application to discover conserved protein complexes among the networks of yeast, worm, fly and Plasmodium, Methods for querying protein networks to explain genetic (synthetic lethal) interactions, Future directions: how network queries will enable systems biology
Reviewed at 2016/01/19